Psychiatric morbidity in individuals with permanent orthopedic disability - Ajay Kumar (Wolters Kluwer Medknow Publications, 2021)
Background: Individuals with permanent orthopedic disability present with a number of physical and mental health issues. Psychiatric illnesses have been seen more frequently among people with disabilities as compared to normal population. Aim: To study psychiatric morbidity among people with permanent orthopedic disability. Materials and Methods: This cross-sectional, observational, hospital-based study was conducted at the department of psychiatry of a tertiary care hospital attached to a medical college during January 01, 2018, to December 31, 2018. The study included subjects over the age of 18 years comprising two groups: Group A (n = 50) including consecutive subjects with orthopedic disability and Group B (n = 50) including normal age- and sex-matched controls. Permission was obtained from the institutional ethics committee before the start of the study. Prior informed consent was obtained from all subjects. Sociodemographic variables were recorded, and psychiatric morbidity was screened on Mini International Neuropsychiatric Interview. Results: 62% (n = 31) of subjects in Group A had psychiatric morbidity as compared to Group B (22%, n = 11). Maximum psychiatric morbidity noted among subjects with disability was generalized anxiety disorder (22%, n = 11), followed by major depressive disorder (20%, n = 10) and alcohol dependence (18%, n = 9). Substance dependence was more in Group A (34%, n = 17) as compared to Group B (18%, n = 9). The most common substance dependence was for alcohol (18%, n = 9), followed by opioids (8%, n = 4) and tobacco (6%, n = 3). Conclusion: Psychiatric morbidity including substance dependence is more common among people with orthopedic disability as compared to normal control subjects.